Cassiope tetragona D. Don - Jarvis, Charlie (Zenodo, 2007)
Andromeda tetragona Linnaeus, Species Plantarum 1: 393. 1753. "Habitat in Alpibus Lapponicis." RCN: 3093. Lectotype (Stone & Stone in Cafferty & Jarvis in Taxon 51: 752. 2003 [2002]): Herb. Linn. No. 166, left specimen (LAPP; iso- G). Current name: Cassiope tetragona (L.) D. Don (Ericaceae). : Published as part of Jarvis, Charlie, 2007, Chapter 7: Linnaean Plant Names and their Types (part A), pp. 252-342 in Order out of Chaos. Linnaean Plant Types and their Types, London :Linnaean Society of London in association with the Natural History Museum on page 290, DOI: 10.5281/zenodo.291971